2014
DOI: 10.1186/s12916-014-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Two age peaks in the incidence of chronic fatigue syndrome/myalgic encephalomyelitis: a population-based registry study from Norway 2008-2012

Abstract: BackgroundThe aim of the current study was to estimate sex- and age-specific incidence rates of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) using population-based registry data. CFS/ME is a debilitating condition with large impact on patients and their families. The etiology is unknown, and the distribution of the disease in the general population has not been well described.MethodsCases of CFS/ME were identified in the Norwegian Patient Register (NPR) for the years 2008 to 2012. The NPR is nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 33 publications
13
83
1
2
Order By: Relevance
“…5 A recent Norwegian study showed 2 age peaks in the incidence of CFS: 10-19 years old and 30-39 years old. 26 They found an incidence of 25.8 per 100,000 person years (95% confidence interval (CI): 25.2 to 26.5), with a female to male incidence rate ratio of 3.2 (95% CI: 3.0 to 3.4).…”
Section: Epidemiologymentioning
confidence: 98%
“…5 A recent Norwegian study showed 2 age peaks in the incidence of CFS: 10-19 years old and 30-39 years old. 26 They found an incidence of 25.8 per 100,000 person years (95% confidence interval (CI): 25.2 to 26.5), with a female to male incidence rate ratio of 3.2 (95% CI: 3.0 to 3.4).…”
Section: Epidemiologymentioning
confidence: 98%
“…This assumption was based on our earlier study of family adversity as a risk factor for chronic disabling fatigue in children at age 13 years 8 and on the gender-related difference in CFS prevalence in adults. 21 Psychological problems, life difficulties, and school attendance (all measured at age 16 years) were considered to be potential risk factors for, or consequences of, CFS at age 16 years. 22,23 …”
Section: Auxiliary Variablesmentioning
confidence: 99%
“…20 The results confirmed the data of the literature with a female:male ratio of 3:1. 21 The Italian National Agency for Regional Health Services (AGENAS) conducted a survey on the prevalence of CFS, using the ICD (International Classification of disease, ninth revision) codes of hospital discharge records between 2001 and 2010. 22 The results led to the conclusion that CFS is not very widespread in Italy with a prevalence in the range of 0.1-0.2%.…”
mentioning
confidence: 99%